P758Cinaciguat prevents diabetes mellitus related cardiac alterations in rats. (15th July 2014) - Matyas, C; Olah, A; Nemeth, BT; Hidi, L; Birtalan, E; Ruppert, M; Kokeny, G; Szabo, G; Merkely, B; Radovits, T
Abstract: Purpose: Diabetes mellitus (DM) is associated with severely impaired nitric oxide (NO) signallig which leads to development of diabetic cardiomyopathy. The second messenger cyclic guanosine monophosphate (cGMP), generated by soluble guanylate cyclase (sGC), plays crucial role in DM related cardiovascular alterations. Improvement of NO - cGMP signalling have been reported to have cytoprotective effects. We investigated the effects of chronic activation of sGC by cinaciguat in diabetic cardiomyopathy in a rat model of type 1 DM. Methods: Type 1 DM was induced by a single i.p. injection of streptozotocin (60mg/kg) in Sprague-Dawley rats. Rats were treated with 10 mg/kg/day cinaciguat (treatment groups) or with placebo (control groups) orally for 8 weeks. Left ventricular (LV) function was assessed using a pressure-volume (PV) conductance microcatheter system in vivo. In addition to our functional experiments, gene expression analysis was performed by qRT-PCR, expression of proteins were assessed by Western blotting (WB). TUNEL assay was carried out to evaluate degree of apoptosis. Cardiac remodelling and fibrosis were investigated by histology and immunohistochemistry. Results: DM was associated with significantly elevated endothelial nitric oxide synthase (eNOS) myocardial expressions while WB proved elevated phosphodiesterase-5 (PDE5) and protein kinase G (PKG) levels and decreased phosphorilated vasodilator-stimulated phosphoprotein - vasodilator-stimulated phosphoprotein (p-VASP/VASP) ratio. We observed increased atrial natriuretic factor (ANF), transforming growth factor-β (TGF-β) and matrix metalloproteinase 9 (MMP-9) levels and fibrotic remodelling of the diabetic heart as evidenced by Masson's trichrome staining. TUNEL assay showed increased apoptosis in DM. Impaired LV contractility (preload recruitable stroke work (PRSW): 49.5±3.3 vs. 83.0±5.5mmHg, p<0.05) and diastolic function (time constant of LV pressure decay (τ): 17.3±0.8 vs. 10.3±0.3msec, p<0.05) were found in the untreated DM group. Cinaciguat treatment prevented DM associated molecular changes and cardiac remodelling and significantly improved systolic (PRSW: 66.8±3.6 vs. 49.5±3.3mmHg, p<0.05) and diastolic (τ: 14.9±0.6 vs. 17.3±0.8msec, p<0.05) function compared to untreated DM. It had no effect in non-diabetic control animals. Conclusions: Our results demonstrate that cinaciguat prevents DM associated myocardial alterations and improves diabetic cardiac dysfunction in rats. Pharmacological activation of sGC might be a novel therapeutic approach for diabetic cardiomyopathy.